The Council of Europe's Reference Framework of Competences for Democratic Culture: Policy context, content and impact (UCL Press, 2020)
The Council of Europe's Reference Framework of Competences for Democratic Culture (RFCDC) was published in April 2018, and is currently being implemented in a number of Council of Europe member states. The RFCDC consists of three main components: a conceptual model of the competences that learners need to acquire in order to respond appropriately and effectively to democratic and intercultural situations; validated and scaled descriptors and learning outcomes for all of the competences in the model; and guidance for ministries of education and education practitioners on curriculum, pedagogy, assessment, teacher education, the whole-school approach, and building learners' resilience to radicalization. This article describes the policy background that motivated and accompanied the development of the RFCDC, and the process through which it was developed. It also provides an overview of the contents of the RFCDC, and an explanation of the impact that the framework is beginning to have on Council of Europe actions in the sphere of formal education.